UTICAJ NASTAVE FIZIČKOG VASPITANJA RAZLIČITIH PROGRAMSKIH SADRŽAJA NA TRANSFORMACIJE MOTORIČKIH SPOSOBNOSTI - Benin Murić; Enver Međedović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
In human existence there is no more supreme and more important task than worrying about healthy posterity. A part of that task and goal is realizing through different forms of movement activities, which we define as physical education. Physical education should contribute to healthiness, happiness and general life capability of our children. Research is done on sample of 300 students from Technical School in Novi Pazar. Goal of this research was to, with help of scientifically verified methods, find out effect of one year long exercising with applying basketball, volleyball and classic physical education on motorical and morphological dimensions of students of first grade in high school. We started the research with general hypothesis that we don't expect any more significant differencies between different groups in motorical and morphological dimensions. Based on one year long experimental treatment under influence of physical education with different program contents we can conclude that there are significant differencies between these groups and that the best results had the group under the influence of educational contents of basketball